TECHNOLOGIES FOR THE BIO FUELS PRODUCTION FOR ENERGY PURPOSE FROM WOOD WASTE - Vangelov, Nikolay (Innovation in Woodworking Industry and Engineering design, 2012)
The paper presents technologies for producing biofuels from wood waste, focusing on ERATO’s strategy for developing affordable biomass fuels suitable for automated residential heating systems. It describes a range of wood‑processing machines including drum chippers, pellet lines, and pellet presses, used to convert various wood residues into energy-efficient fuels. The study highlights the technical capabilities of this equipment and its role in expanding sustainable biofuel production in Bulgaria.